PENGGUNAAN RADEC LEARNING DALAM PEMBELAJARAN SEJARAH: SYSTEMATIC LITERATURE REVIEW - Nashar; Rikza Fauzan; Wulan Nurjanah (Kilau Publishing, 2026)
The RADEC (Read, Answer, Discuss, Explain, Create) learning model was developed as a learning approach that emphasises active student engagement through explicit and systematic stages. This study aims to examine the use of the RADEC learning model in history education through a systematic literature review (SLR) approach. Data were obtained from Google Scholar using the Publish or Perish application with the keyword ‘RADEC’ and limited to publications from 2015 to 2025. Of the 100 articles collected, only 9 were relevant to the topic of history learning, and after selection based on inclusion criteria, only one article met the analysis requirements. The article demonstrated that the application of RADEC significantly improved students' learning outcomes in the subject of Islamic Cultural History. The findings also highlighted challenges in implementing RADEC, such as low student reading interest and insufficient teacher readiness. However, the simple and contextual syntax of RADEC makes it relevant and effective for implementation. This study concludes that although research is still limited, the RADEC model has great potential in supporting active history learning oriented towards 21st-century skills. Further research is recommended to expand the understanding and implementation of RADEC in the context of history at various levels of education. Keywords: RADEC, history learning, systematic literature review, learning effectiveness